EPCO-03. GLIOMA ONCOGENESIS IN THE CONSTITUTIONAL MISMATCH REPAIR DEFICIENCY (CMMRD) SYNDROME. (12th November 2021) - Guerrini-Rousseau, Léa; Merlevede, Jane; Denizeau, Philippe; Andreiuolo, Felipe; Varlet, Pascale; Puget, Stéphanie; Beccaria, Kevin; Blauwblomme, Thomas; Cabaret, Odile; Hamzaoui, Nadim; Bourdeaut, Franck; Faure-Conter, Cécile; et al.
Abstract: PURPOSE: Constitutional Mismatch Repair Deficiency (CMMRD) is a cancer predisposition due to bi-allelic mutations in one of the four main mismatch repair (MMR) genes ( PMS2, MSH2, MSH6 or MLH1 ) associated with early onset of cancers, especially glioblastomas (GBM). Our aim was to decipher the molecular specificities of gliomas occurring in this context. METHODS: A comprehensive analysis of clinical, histopathological and genomic data (whole exome sequencing) was performed for 12 children with a CMMRD for which we had available frozen brain tumor material (10 GBM and 2 anaplastic astrocytomas). RESULTS: Eight patients harbored an ultra-mutated phenotype with more than 100 somatic non synonymous (NS) SNV/Mb. No correlation was observed between the number of mutation and sex, age, overall survival or mutated MMR gene. POLE and POLD1 exonuclease domain driver somatic mutations were described for eight and one patients respectively. The 4/12 tumors without POLE somatic mutation did not show the classical ultra-hypermutation pattern. All patients with POLE mutation had already more than 20 NS SNV/Mb (median 40NS SNV/Mb, [range 23-114]) suggesting that the hypermutation phenomenon started before the appearance of the somatic POLE mutation. The mutational signatures of the tumors, dominated by the MMR signatures, were not modified after the onset of the POLE mutation when analyzing the different mutation bursts. Specific recurrent somatic mutations were observed in SETD2 (9/12), TP53 (9/12), NF1 (9/12), EPHB2 (8/12), and DICER1 (7/12). Only half of the tumors overexpressed PDL1 by immunohistochemistry and this overexpression was not associated with a higher tumor mutation burden. CONCLUSION: CMMRD-associated gliomas have a specific oncogenesis that does not trigger usual pathways and mutations seen in sporadic pediatric or adult GBM. Frequent alterations in other pathways ( e.g. MAPK or DNA-PK pathway) may suggests the use of other targeted therapies aside from PD1 inhibitors.